2016
DOI: 10.1108/aaaj-07-2015-2141
|View full text |Cite
|
Sign up to set email alerts
|

Rana Plaza collapse aftermath: are CSR compliance and auditing pressures effective?

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
185
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(200 citation statements)
references
References 55 publications
9
185
1
5
Order By: Relevance
“…Indeed, our analysis supports Sinkovics et al's (2016) conclusions as to the nature of the garment industry in Bangladesh. This is that the copper mining sector in Zambia holds a paradoxical role in this country as it is both a heavy contributor to the country's economic development but also that it acts as a potential obstacle to its future development .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Indeed, our analysis supports Sinkovics et al's (2016) conclusions as to the nature of the garment industry in Bangladesh. This is that the copper mining sector in Zambia holds a paradoxical role in this country as it is both a heavy contributor to the country's economic development but also that it acts as a potential obstacle to its future development .…”
Section: Discussionsupporting
confidence: 82%
“…They cite clear evidence of what they term the "state-business nexus" in perpetuating human rights disasters, with "this nature of the state creat[ing] the necessary conditions for businesses to disregard human rights in businesses" (Siddiqui and Uddin, 2016, p. 696). Moreover, given the existence of weak institutions, high rates of corruption and the inability of governments to implement regulations (Visser, 2006), there have been increased calls for "surrogate accountability" in developing countries (Sinkovics et al, 2016). Such surrogates, which can take a variety of forms (governments, supra-national bodies, partnerships among corporations or civil society) may be better equipped to pressurise power wielders to do what is "right" (Rubenstein, 2007).…”
Section: Theoretical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoréglementée par nature, l'application des normes sociales trouve sa source dans la mission de responsabilité sociale des entreprises. Dans les chaînes d'approvisionnement complexes, les multinationales jouent le rôle de prescripteurs en matière de responsabilité, imposant de l'extérieur des normes de conduite en matière de reddition de comptes et d'audit à leurs fournisseurs de pays en développement (Sinkovics, Hoque et Sinkovics, 2016). La responsabilité sociale est à présent une énorme industrie, qui représente entre 15 et 80 milliards de dollars des États-Unis par an, et fait appel à nombre de grandes sociétés internationales d'audit et d'organisations indépendantes à but non lucratif (Terwindt et Armstrong, 2019).…”
Section: Les Limites De La Gouvernance Privée Et Des Dispositifs De Runclassified
“…Sinkovics, Hoque and Sinkovics (2016) found that the pressure for compliance has led the case companies to priorities the implementation of measurable standards over the socially grounded needs and priorities of workers. As such instead of adding new social value in fact destroyed previously existing social value as well as the pressure for compliance created the necessity to find ways to cover the sizable cost of compliance [16].…”
Section: Case Of Rana Plaza Tragedymentioning
confidence: 99%